Transactional Sex Amongst AIDS-Orphaned and AIDS-Affected Adolescents Predicted by Abuse and Extreme Poverty - Cluver, L.; Orkin, M.; Boyes, Mark; Gardner, F.; Meinck, F. (Lippincott Williams & Wilkins, 2011)
Objectives: Little is known about impacts of familial AIDS on abuse and sexual health outcomes amongst adolescents. Objectives were to determine whether familial AIDS is: (1) associated with severe physical, emotional, and sexual abuse; (2) associated with transactional sexual exploitation; and (3) explore whether relationships between familial AIDS and transactional sex are mediated by extreme poverty and abuse. Design: Adolescent self-report study in deprived South African communities. Methods: A 2009 follow-up of a 2005 study achieved 71% retention (n = 723). The 2009 sample included AIDS-orphaned (n = 236), other orphaned (n = 231), and non-orphaned (n = 220) adolescents, whose primary caregivers were AIDS sick (n = 109), other sick (n = 147),and healthy (n = 220). Abuse and transactional sex were measured using widely used and validated self-report measures. Results: AIDS orphanhood and parental AIDS sickness predicted emotional and physical abuse and transactional sexual exploitation. Orphanhood or parental sickness by non-AIDS causes, and having healthy caregivers, did not predict any abuse outcomes. Adolescents “dually” affected by AIDS orphanhood and sickness showed a 3-foldlikelihood of severe emotional and physical abuse and, amongst girls, a 6-fold likelihood of transactional sexual exploitation, compared with those in healthy families. Heightened risk of transactional sex amongst adolescents in AIDS-affected families was mediated by extreme poverty and abuse exposure. In combination, the effects of familial AIDS, food insecurity, and exposure to abuse raised prevalence of transactional sex amongst girls from 1% to 57%.Conclusions: Adolescents from AIDS-affected families are highly vulnerable to severe physical and emotional abuse and transactional sex. This has implications for policy and programming in child protection and HIV prevention services.